Studies on Complexes of Cu(II), Ni(II), Co(II) and Ln(III) with 3-(α-Benzoyl) Benzylidenehydrazino-5,6-Diphenyl-1,2,4-Triazine - A.T. Ramadan, Atef; M. Abdel-Rahman, Reda; Saeda, H. Magdy (Asian Journal of Chemistry, 2010)
The synthesis, acid-base equilibria and metal-ion chelating tendencies of 3-(et-benzoyl) benzylidenehydrazino-5,6-diphenyl-1,2,4-triazine (BHT) are reported. From potentiometric equilibrium measurements of hydrogen-ion concentration at 30ºC and ionic strength 0.10 M KNO3 in 75% (v/v) dioxane-water medium, the values of the stability constants of BHT with transition and lanthanide(III) ions have been evaluated. Probable structures of metal chelates are inferred from electronic absorption spectra and infrared examination of solid complexes. The use of BHT as analytical reagent for the spectrophotometric determination of copper, nickel and cobalt has also been discussed.